2010
DOI: 10.1007/s10530-010-9884-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for predatory control of the invasive round goby

Abstract: We coupled bioenergetics modeling with bottom trawl survey results to evaluate the capacity of piscivorous fish in eastern Lake Erie to exert predatory control of the invading population of round goby Neogobius melanostomus. In the offshore ([20 m deep) waters of eastern Lake Erie, burbot Lota lota is a native top predator, feeding on a suite of prey fishes. The round goby invaded eastern Lake Erie during the late 1990s, and round goby population size increased dramatically during 1999-2004. According to annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 35 publications
2
59
0
1
Order By: Relevance
“…Round goby energy density along with potential piscivorous competitors such as fish (i.e. burbot (Lota lota), walleye (Sander vitreus), smallmouth bass (Micropterus dolomieu), and northern pike (Esox lucius; Madenjian et al, 2011;Reyjol et al, 2010;Weber et al, 2011)) and other waterbirds (i.e. Red-breasted Merganser (Mergus serrator) Bur et al, 2008) could allow for less invasive control of DCCO populations.…”
Section: Discussionmentioning
confidence: 99%
“…Round goby energy density along with potential piscivorous competitors such as fish (i.e. burbot (Lota lota), walleye (Sander vitreus), smallmouth bass (Micropterus dolomieu), and northern pike (Esox lucius; Madenjian et al, 2011;Reyjol et al, 2010;Weber et al, 2011)) and other waterbirds (i.e. Red-breasted Merganser (Mergus serrator) Bur et al, 2008) could allow for less invasive control of DCCO populations.…”
Section: Discussionmentioning
confidence: 99%
“…One inevitable consequence of biological invasions is the alteration of predator-prey interactions. Hyper-successful non-indigenous species (hereafter referred to as invasive species) are a ubiquitous component of the diet of native predators (e.g., King et al 2006;Johnson et al 2010a, b;Madenjian et al 2011) and it is clear that native predators can rapidly shift their diet to feed on invasive prey (Carlsson et al 2009). Despite the growing tendency of native predators to forage on invasive species, the population response of native predators to changes in prey base remains largely unknown (Carlsson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Combined, these studies suggested the diet shift that we have documented in this study and support the predominance of round goby in the current diet of Lake Michigan burbot. Madenjian et al (2011) showed a similar diet shift to round goby in Lake Erie and were able to demonstrate predatory control of the species by predators, including burbot, though this has not yet been shown in Lake Michigan. Several of these studies also reported the importance of rainbow smelt and other small species in burbot diet, which we did not observe in our study although a decrease in smelt populations is coincident with the beginning of our study period (Fratt et al, 1997;Jacobs et al, 2010).…”
Section: Discussionmentioning
confidence: 89%